Dr. Guglielmo Rufolo - Rufolo, Guglielmo (DEEPPLANE™ surgeon registry, 2026)
Surgeon profile record for Dr. Guglielmo Rufolo, practicing in Rome, Italy. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
CC-BY-4.0 licensed; published by DEEPPLANE™
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; italy; rome